Validating an instrument on application of the Prophet's Mohammed instructional strategies model in the Kulliyyah of Islamic Revealed Knowledge and Human Sciences at IIUM - Yussuf, Abdiweli Mohamed (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The primary objectives of this study were to validate an instrument on application of the Prophet Mohammed (P.B.U.H.) instructional strategies model in the Kulliyyah of Islamic Revealed Knowledge and Human Science (KIRKHS) at International Islamic University Malaysia (IIUM). The researcher implemented a quantitative design which involves the use of numerical indices. A total of 484 respondents answered the questionnaires, the researcher employed the survey method to gather data associated with prophetic instructional strategies and its application in the KIRKHS. A questionnaire of fifty (50) items was created from the framework/model extracted from the review of literature and 7-Likert scale technique was used. The quantitative data collected was coded and analyzed using the Statistical Package for the Social Science (SPSS) version 20 for exploratory factor analysis (EFA) and Analysis of Moment Structures (AMOS) version 18 for confirmatory factor analysis (CFA). The findings revealed six inter-correlated factors (Role model, Multiple Intelligences, Evaluation and Assessment, Variety of teaching methods, Motivation and considering differences) that were revealed by the EFA. Although, the factors produced by EFA were retained but the measures were furthered reduced in CFA analysis. Replication of EFA factors by CFA is an indication of adequate psychometric properties of construct. Furthermore, this study confirmed that students from male and female groups, both age groups of old and young samples and both year of study groups have received the same pattern of teaching based on the Prophet Mohammed (P.B.U.H.) instructional strategies. Therefore, the study ascertained that the six-factor model of prophetic instructional strategies did show a relatively acceptable level and was adequate. For study contributions, in the aware of the researcher, this study is the first of its kind examining and validating the prophetic instructional strategies model in such academic application (KIRKHS, IIUM). So, it contributes to the literature on pedagogy by providing a prophetic model taken from the traditional Sunnah. Furthermore, the result of this study can be further developed to achieve Islamic theories in the field of teacher education. Finally, the researcher displayed the recommendations proposed by the study based on the results that have been reached.